Avaliação no ensino e aprendizagem da matemática - Silva, Sandro Machado (2014)
The dissertation approached the subject evaluation in teaching and learning mathematic sander search problem was to determine which evaluative criteria may be developed by teacher son issues of mathematics drawn from national and international asses sments in a workshop one valuation in volving teachers from a school in Santa Maria in Rio Grande do Sul. It was investigated in what ways these teachers establish evaluative criteria for issues of Mathematics and how they evaluate these questions taken from PISA, ENEM and PROOF BRAZIL. Besides this we attempted to check how teachers are using assessment in their teaching and how they see the error of the student in resolving these issues. Data were collected through questionnaires and application of an instrument containing questions for teachers would use the same on the resolution was judged convenient to subsequently establish their criteria. Research results showed that one of the teachers presents classical trend, one has trend technicist and two give evidence constructivist trend. One of the teachers, although it solved the issues properly, like the others, did not present any evaluation criteria. Thus, it is understood that the purpose of the dissertation research on assessment in mathematics from a workshop with teachers of Mathematics in Basic Education was fulfilled .